2001
DOI: 10.1086/320499
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray–emitting QSO[CLC]s[/CLC] Ejected from Arp 220

Abstract: Four compact ROSAT X-ray sources very close to the nearby ultraluminous infrared galaxy Arp 220 (IC 4553) have been identified as medium-redshift QSOs. The closest pair lying symmetrically across the galaxy have almost identical redshifts z = 1.25, 1.26. All of the evidence suggests that these QSOs have been ejected from Arp 220 and have large intrinsic redshifts.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Moreover, they are point-like objects (FWHM equal to the seeing: ≈1.0 ) which is another expected feature in this kind of objects. Other authors (Burbidge 1995(Burbidge , 1997Arp et al 2001) have also reported the detection of quasars/Seyferts 1 apparently ejected by a parent Seyfert galaxy.…”
Section: Discrepant Redshiftsmentioning
confidence: 90%
“…Moreover, they are point-like objects (FWHM equal to the seeing: ≈1.0 ) which is another expected feature in this kind of objects. Other authors (Burbidge 1995(Burbidge , 1997Arp et al 2001) have also reported the detection of quasars/Seyferts 1 apparently ejected by a parent Seyfert galaxy.…”
Section: Discrepant Redshiftsmentioning
confidence: 90%
“…The pattern of quasars of similar redshift paired across active and ejecting galaxies of much lower redshift has been recorded many times now (Arp, 1967(Arp, , 1998(Arp, , 2003Burbidge, 1997;Radecke, 1997;Arp et al, 2001Arp et al, , 2002. Quasars also have been associated with radio and X-ray ejections from the beginning.…”
Section: Relation To Previous Associations Of Quasars With Low Redshimentioning
confidence: 82%
“…Existence of periodicities in the redshift (Þ) distribution of QSOs has been claimed since a long time (Burbidge & Burbidge 1967;Cowan 1969;Lake & Roeder 1972;Burbidge & O'Dell 1972;Barnothy & Barnothy 1976;Karlsson 1977Karlsson , 1990Arp et al 1990), while peaks and troughs in the Þ-distribution that are responsible for exhibiting periodicities have also been shown to be due to the presence of various selection effects (Basu 1973(Basu , 1975(Basu , 1978a(Basu , 1978b(Basu , 1985(Basu , 1992(Basu , 1999Willy & Ricklefs 1976;Box & Roeder 1984;Scott 1991). These studies include samples involving the total number of QSOs known at that time, as well as individual samples of QSOs spanning limited redshift ranges.…”
Section: Introductionmentioning
confidence: 99%
“…A × is a quantitative measure of search lines available for identification with observed lines and is computed as the number of search lines (with 'weights' between 0 to 2) lying within the observing window at a particular redshift range (Basu 1973). A × has explained (Basu 1999) the peaks and troughs in the redshift distribution for individual samples of Arp et al (1990) and Karlsson (1990). It may be mentioned that one of the two samples in Karlsson (1990), viz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation